Sejarah, Urgensi dan Tipologi Pencatatan Perkawinan dalam Undang-undang Keluarga Islam di Negara Muslim - Habib Shulton Asnawi (Bulletin of Community Engagement, 2024)
This article discusses the history and urgency of marriage registration regulations in Islamic family law in Muslim countries. The background to writing this article is a phenomenon that emerged in the Islamic world in the 20th century, namely efforts to reform family law carried out by countries with Muslim majority populations. Family law reforms carried out by various Muslim countries generally cover three aspects, namely marriage, divorce and inheritance. In the context of marriage, one form of reform carried out is marriage registration. Juridically, the requirements for marriage are: first, material requirements, namely the conditions attached to each marriage pillar, both those regulated in jurisprudence and those regulated in legislation. Second, administrative requirements, namely requirements related to marriage registration. However, the addition of marriage registration as a condition for a marriage has given rise to debate. The focus or problem formulation in this article is: 1). What is the history of marriage registration regulations? 2). What is the typology of marriage registration rules in Islamic family law in Muslim countries? 3). What is the urgency of the marriage registration regulations?